Žuvų taukų gamyba iš atlantinės lašišos (Salmo salar) šalutinių produktų, fermentinės hidrolizės būdu - Ivanskytė, Gintarė; Šilas, Giedrius (2024)
In the last few years, the increased demand for healthy food has increased the capacity of fish processing units, and with it, the volume of by-products (heads, internal organs, bones) has also increased. More than 70% of all fish caught are further processed in the food industry before being put on the market, so muscle scraps (15-20%), skin and fins (1-3%), bones (9-15%), heads ( 9-12%), viscera (12-18%) and scales (5%), in terms of nutritional value, a huge loss of nutrients. One of the many ways of processing fish offal is the production of fish oil. Fish oil is a rich natural source of omega-3 polyunsaturated fatty acids (PUFA), mainly eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). The enzymatic hydrolysis method is one of the most researched, green production methods and is an ideal way to extract fat and protein from fish and its by-products.